VAPE IS NOT A SAFE ALTERNATIVE: STRENGTHENING ADOLESCENTS’ AWARENESS THROUGH MEDICAL AND ISLAMIC-BASED EDUCATION AT SMK PGRI 13 SURABAYA - Dewi Masithah; Mia Puspitasari; Muhammad Fifin Kombih; Sabrina Cantika Aura; Puspita Rahmatul Jinan; Ain Darojah Siddiq Ramadhana (Institute for Research and Community Service, Health Polytechnic of Kerta Cendekia, Sidoarjo, 2025)
In recent years, a worrying shift has occurred from conventional cigarettes to electronic cigarettes (vapes), which are often perceived as safer. However, evidence indicates that vape liquids contain nicotine, formaldehyde, and toxic chemicals capable of causing addiction, neurodevelopmental harm, and lung injury in adolescents. This community service project aimed to increase students' awareness regarding the dangers of conventional cigarettes and electronic cigarettes (vapes) through an integrated medical and Islamic-based educational approach. The program was conducted at SMK PGRI 13 Surabaya and included interactive lectures, video presentations, group discussions, leaflet distribution, personal reflection, selection of youth anti-smoking ambassadors, and basic health screening. Knowledge evaluation was conducted using pre and posttests. The results showed an increase in students' knowledge scores from 77 to 87 (a 12% improvement). Nutritional status assessment among 76 students showed 36.8% were in the normal BMI category, 26.3% underweight, 11.8% overweight, and 25% obese. Several active smokers expressed commitment to quitting smoking, and student anti-smoking ambassadors were appointed to promote a smoke-free environment. This program demonstrates that integrating health education with Islamic values effectively enhances adolescents’ awareness and motivation to avoid smoking and vaping. The sustainability of the initiative is supported by school involvement and the empowerment of peer ambassadors.